In-vivo and in-vitro impact of high-dose rate radiotherapy using flattening-filter-free beams on the anti-tumor immune response. (September 2020) - Laurent, P.A.; Kownacka, A.; Boidot, R.; Richard, C.; Limagne, E.; Morgand, V.; Froidurot, L.; Bonin, C.; Aubignac, L.; Ghiringhelli, F.; Créhange, G.; Mirjolet, C.
Highlights: Effect of RT dose rate modulation on immune response has never been evaluated. Preclinical study using FFF RT technique in vivo and in vitro. RT dose rate did not influence radio-immune response parameters. We may modulate RT dose rate in association with immunotherapy without efficacy modification. Abstract: Introduction: Modern accelerators have the "flattening filter-free" (FFF) technique to deliver RT with a moderate high-dose rate, currently used in limited clinical indications. No scientifically established data are currently available on the possible effects of this high dose rate on the anti-tumor immune response. We therefore propose here to study these effects in a preclinical CT26 murine colorectal tumor model. Material and methods: In-vitro, CT26 cells were irradiated on a Varian TrueBeam® linac at 3 different dose rates (4; 12 or 24 Gy/min) using the FFF mode. Activation of the anti-tumor immune response was evaluated by the analysis of induction of genes of the type I interferon pathway by RT-qPCR, and by the study of the induction of immunogenic death biomarkers. In-vivo, an efficacy study of RT delivering 16.5 Gy at 2 different dose rates was performed in immunocompetent Balb/c mice carrying CT26 syngeneic tumors, as well as an immunomonitoring analysed by flow cytometry and a transcriptomic analysis using RNA sequencing. Statistical analyzes were performed using non-parametric tests. Results: In-vitro, no significant influence of an increase in FFF dose rate was shown for the induction of genes of the type I interferon pathway as well as for the studied immunogenic death markers (HMGB1 secretion). In-vivo, no difference in terms of tumor growth retardation between the 2 dose rates used was demonstrated, as well as for the composition of immune cell infiltrates within tumor microenvironment and the expression of immune checkpoints in immunomonitoring and RNAseq. Conclusion: In this study involving the CT26 model, no influence of a moderate high dose rate in FFF technique on the anti-tumor immune response was demonstrated, which would make studies of associations between RT and checkpoint inhibitors fit with this technique of RT. However, further explorations using other cellular models seem to be of interest.